Changes in cardiac structure and function among elite judoists resulting from long-term judo practice - Laskowski, R.; Wysocki, K.; Multan, A.; Haga, S. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The aim of this study was to investigate the character of changes in cardiac structure and function among elite judoists due to long-term judo practice. Methods. A group of male (N=20, average age: 22.1) and female (N=15, average age: 19.4) athletes practising judo for about 10 years was subjected to echocardiographic tests carried out during rest (aorta diameter [AoD], diastolic dimension of the left ventricle [Dd], thickness of the interventricular septum [IVST], the thickness of the posterior wall of the left ventricle [LVPWT]), and to measurement of cardiovascular system's action parameters (heart rate [HR], stroke volume [SV], cardiac output [Q], blood pressure [BP]). Moreover, control non trained subjects were also studied, women (N=30, average age: 19.1) and men (N=30, average age: 21.4). In order to determine aerobic efficiency, the authors measured the maximal oxygen uptake (VO2max) using the direct method. The anaerobic capacity was estimated on the basis of the maximal anaerobic power, and the volume of the performed work was calculated by means of the 30 s Wingate test. Results. Echocardiographic test values imply that changes in heart morphology induced by long term judo training, such as increase diastolic dimension of the left ventricle, thickness of the interventricular septum and left ventricular posterior wall, resemble more the changes observed in endurance athletes than changes observed in strength athletes. Conclusion. The obtained data indicated that judo training improves both aerobic and anerobic performance and these changes were associated with changes in heart structure and function as compared to non trained control.